Factors Impacting University Majoring in Vocal Music Students’ Behavioral Intention to Chaoxing Learning Platform In Changsha, Hunan, China - Fan, Jinchao; Li, Changhan; Chen, Yinhua (Scholar: Human Sciences, 2024)
Purpose: The purpose of this study was to determine students’ behavioral intention to Chaoxing learning platform. The study was conducted in public primary university in Changsha, Hunan Province, China, with majoring vocal students who had at least one year of experience using this technology. Research design, data and methodology: This is a quantitative study, which uses survey to collect sample data through a set of questionnaires to explore the factors influencing the Behavioral Intention of using Chaoxing learning platform for vocal music majors in university. The questionnaire is made by online questionnaire of Kingsoft Form with 500 sample size. The content validity method of Item Objective Congruence (IOC) Index was used, resulting all measuring items reserved by three experts. Pilot testing of 30 participants was approved under Cronbach’s Alpha reliability test at a score of 0.7 or over. Confirmatory Factor Analysis (CFA) and Structural Equation Model (SEM) were performed for data analysis, including goodness of model fits, validity, and reliability testing. Results: The results show Perceived Enjoyment, Self-Efficacy, Teacher Support, Perceived Ease, Perceived Usefulness, Perceived Ease of Use and Attitude all support the model. Conclusions: This study has a relevant role in promoting the service of Chaoxing platform and the improvement of related technologies.